2015
DOI: 10.3109/14992027.2015.1074735
|View full text |Cite
|
Sign up to set email alerts
|

Development and evaluation of the Turkish matrix sentence test

Abstract: The TURMatrix was developed according to European standards and provides reliable speech intelligibility measurements in noise and quiet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 23 publications
0
39
0
4
Order By: Relevance
“…Его также называют Ольденбургским фразо-вым тестом (Oldenburger Satztest, OLSA). На настоящий момент существует 18 версий данного теста для разных языков, из которых 9 доступно для клинического исполь-зования [12][13][14][15][16][17][18]. С 2012 г. начались испытания русской версии матриксного фразового теста (Russian matrix sentence test), которая получила сокращенное название RuMatrix Test.…”
Section: оригинальные статьиunclassified
“…Его также называют Ольденбургским фразо-вым тестом (Oldenburger Satztest, OLSA). На настоящий момент существует 18 версий данного теста для разных языков, из которых 9 доступно для клинического исполь-зования [12][13][14][15][16][17][18]. С 2012 г. начались испытания русской версии матриксного фразового теста (Russian matrix sentence test), которая получила сокращенное название RuMatrix Test.…”
Section: оригинальные статьиunclassified
“…However there is a correlation between the Non-adaptive Intelligibility Score in Quiet and the Adaptive Matrix SRT in Quiet values (p<0.05). Similarly, Zokoll et al (11) did not report any significant correlation between SRT in quiet (dB SPL) and adaptive SRT in noise (dB SNR).…”
Section: Comparison Between Normal Hearing Subjects and CI Usersmentioning
confidence: 99%
“…Although a similar study for Turkish CI users could not be found, Zokoll et al (11) measured the intelligibility scores at fixed SNRs in normal hearing subjects using the Turkish Matrix test. Then they calculated the mean SRT value of subjects and found that the subjects has a speech intelligibility score of 50% at -8.3 +/-0.2 dB SNR.…”
Section: Comparison Between Normal Hearing Subjects and CI Usersmentioning
confidence: 99%
See 2 more Smart Citations